How Do Competition Policy and Data Brokers Shape Product Market Competition? - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2018)
This paper empirically analyzes how a data broker affects competition in oligopolistic product markets. It examines a unique case concerning the two dominant Finnish food retail companies' voluntary withdrawal from information exchange via a data broker. Moreover, the companies jointly approached the Finnish antitrust authority, originating an investigation whether their prior horizontal information exchange was illegal. This resulted in the permanent termination of a data broker's business in the Finnish food retail sector. The empirical analysis employs quarterly data from the food retail sector of the old EU15 countries for 2005–2017. The difference-in-differences model is used to explore the competitive impacts of a termination of vertical and horizontal information exchange via a data broker in the Finnish food retail sector. Data suggest that competition was less fierce and product prices higher after the termination of information exchange via a data broker. Longer-term evidence on the price increase in the absence of a data broker is inconclusive. Furthermore, discontinuation of data exchange from the downstream to the upstream firms facilitated downstream bargaining power and generated a long-term increase in the gap between retail and producer prices.
Keywords: L11; L13; L41; L81; 330; Data brokers; Market for data; Competition; Competition policy